2023
DOI: 10.3390/en16134994
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Studies on Minimum Miscibility Pressure for n-Decane and CO2

Abstract: Oil production is a complex process that can be made more efficient by applying gas enhanced oil recovery (EOR) methods. Thus, it is essential to know the minimum miscibility pressure (MMP) and minimum miscibility enrichment (MME) of gas in oil. Conventional slim-tube experiments for the measurement of MMP require hundreds of millilitres of real or recombined oil and last over 30 days. Advances in microfluidic technology allow the reduction of the amount of fluid and the time required in determining MMP (or MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…After 1 PV of CO 2 injection, the oil inside the dead-end pore was still bypassed and required a longer injection time to be extracted. The pure CO 2 and decane mixed at the first contact, unlike reservoir oil, in which multiple contact miscibility could be developed through a component exchange . The miscible CO 2 injection into Varsol oil was conducted, and it was concluded that the CO 2 finger flowed into the micromodel and effectively swept oil out at the occupied area .…”
Section: Resultsmentioning
confidence: 99%
“…After 1 PV of CO 2 injection, the oil inside the dead-end pore was still bypassed and required a longer injection time to be extracted. The pure CO 2 and decane mixed at the first contact, unlike reservoir oil, in which multiple contact miscibility could be developed through a component exchange . The miscible CO 2 injection into Varsol oil was conducted, and it was concluded that the CO 2 finger flowed into the micromodel and effectively swept oil out at the occupied area .…”
Section: Resultsmentioning
confidence: 99%
“…Traditional experimental methods for determining MMP mainly include the slim tube experiment (ST) [95], rising bubble method (RBA) [96], and the disappearance of interfacial tension method (VIT) [97]. However, these experimental methods are time-consuming, subjective, lack quantitative information, and are not suitable for complex mixtures [98]. Theoretical methods simulate the situations of immiscible and miscible phases by coupling the Navier-Stokes equation, interface tracking equation, and convection-diffusion equation, or calculating critical parameters using state equations.…”
Section: Minimum Miscibility Pressurementioning
confidence: 99%
“…On the one hand, the application of CO 2 flooding can store CO 2 in the reservoir and reduce CO 2 emissions, playing a significant role in environmental protection. On the other hand, except for low cost, it has great potential to improve oil recovery for CO 2 flooding, which can bring significant economic benefits. …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, except for low cost, it has great potential to improve oil recovery for CO 2 flooding, which can bring significant economic benefits. 1 4 …”
Section: Introductionmentioning
confidence: 99%